1993
DOI: 10.1177/0013164493053004010
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Tendency to Gossip Questionnaire: Construct and Concurrent Validation for a Sample of Israeli College Students

Abstract: A newly-developed 20-item Tendency to Gossip Questionnaire (TGQ) is described. TGQ scores were normally distributed and showed high internal consistency (.87) for a sample of 120 students (58 female, 62 male). TGQ scores for females were significantly higher than those for males. The TGQ was validated against peer ratings using 30 kibbutz members. The TGQ's relationship to social desirability and vocational interest in people-oriented professions were studied. Four possible subscales of gossip content emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 11 publications
3
61
0
3
Order By: Relevance
“…As predicted, self‐monitoring was related to gossip with correlations of .30 and .25, respectively, with the GFQ (Foster, 2004) and the TGQ (Nevo et al., 1993, 1994). Self‐monitoring was also negatively related to self‐concept clarity ( r = −.29).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…As predicted, self‐monitoring was related to gossip with correlations of .30 and .25, respectively, with the GFQ (Foster, 2004) and the TGQ (Nevo et al., 1993, 1994). Self‐monitoring was also negatively related to self‐concept clarity ( r = −.29).…”
Section: Resultssupporting
confidence: 63%
“…The achievement subscale of the TGQ (Nevo et al., 1993, 1994) and the influence subscale of the GFQ (Foster, 2004) were the most strongly related factors of gossip to low self‐concept clarity. These relationships are evidence of the use of discussing famous people, which is the majority of the content of the achievement subscale and using gossip as a form of influence on others to gain power and a clearer sense of self.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little empirical evidence that women gossip more frequently than men (cf. Dunbar, 1993aDunbar, , 1994Eckert, 1990;Foster, 2003;Haviland, 1977;Levin & Arluke, 1985;Loudon, 1961;Nevo, Nevo, & Derech-Zehavi, 1993); in general, any reported differences between the sexes are small. Thus, with current data, it is not easy to get a precise fix on the amount of time that people spend gossiping.…”
mentioning
confidence: 90%
“…8 Nevo et al 9 tested for differences in the gossip tendencies of men and women. They also speculated that had they asked about gossip about the sports achievements of others as opposed to physical appearance of others, they would have found that men gossip more than women.…”
Section: Introductionmentioning
confidence: 99%